Mode of Operation of the Republic of Moldova Power System with Back-to-Back Installation at the Substation Vulcanesti - Postolaty V.; Berzan V.; Bykova Elena; Andronaty N. (Problems of the Regional Energetics, 2016)
The results of analysis of the operating mode of power system of the Republic Moldova when accomplishing the interconnection with the power system of Romania using the Back-to-Back (BtB) power unit at the transformer station Vulcanesti have been presented in the paper. Installation of BtB leads to the loading of overhead power line (OPL) 330kV Vulcanesti-Chisinau up to 571 MW with the change of the value and the direction of power flux in OPL from Chisinau toward Kuchurgan power station, the decrease of power flux entering the north of the country (OPL 330kV HPP Dnestrovsk - Balti) and in the OPL 330kV (Kotovsk- Kuchurgan power station). Essential changes of the active power flux occur at the buses of Kuchurgan power station toward Ukraine in comparison with the actual topology of power network (base regime). The change of the direction and of values of power flux through the unified power system has as a consequence the increase by 171MW (from 2961MW to 3132MW), as well as the increase by 7,1% of the losses of power in high voltage Moldovan network comparing with the base regime. It is pointed that the accomplishment of asynchronous interconnection with Romania has the impact at regional scale causing the change of power fluxes both in the power system of the Republic of Moldova and of Ukraine with Romania including the Kuchurgan power station. Assessment of financial aspects indicates to the trend of increasing of the project’s cost of the interconnection with Romania, but in the case of investment return considering the increase of the cost for the service of transmission of power is expected the necessity to increase the tariff with nearly 154% in comparison with the value of 2015 year, considering zero value of bank and inflation rates during the 10 years of investment return, as well as the constant exchange rate of MDL to EURO during the 10 years investment return period.